Ekspansi Perkebunan Kelapa Sawit Politik Ekologi - Maggara, Tomi Satria; Magriasti, Lince (AHKAM, 2024)
The aim of writing this article is to look at the Expansion of Palm Oil Plantations, Ecological Politics. As a consequence of the large-scale expansion of oil palm plantations, the community is also caught up in the euphoria of oil palm plantation expansion. This research found a form of silent expansion carried out by independent farmers/plantations. Silent expansion is a strategy to expand oil palm plantations which is carried out secretly, illegally (behind the state's backstage), small-fragmented areas, and carried out by farmers/plantations who have relationships with actors such as the middle man and the big man. The data collection technique for this research is a library research library study sourced from various reading literature and previous research articles regarding political ecology. The expansion of oil palm plantations in forest areas also has an impact on changes in the ecological landscape and changes in land use, changes in land cover as well as several serious environmental problems such as depletion of soil nutrients and increased carbon emissions due to deforestation and emissions inherent in the processing of oil palm fruit.